1986
DOI: 10.1530/jrf.0.0760339
|View full text |Cite
|
Sign up to set email alerts
|

Uterine and embryonic metabolism after diapause in the tammar wallaby, Macropus eugenii

Abstract: The early reactivation of the uterus and embryo from diapause suggests that it is not triggered by the previously described peaks of progesterone and oestradiol in plasma at Day 5, although there may be an earlier, increased sensitivity to these steroids which allows uterine reactivation to precede changes in peripheral plasma concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 20 publications
1
35
0
Order By: Relevance
“…Since it has been shown that the conceptus is associated with the peripartum prolactin peak (Tyndale-Biscoe et ai, 1988) the present results suggest that the fetus or its membranes induces this by initiating the release of PGs, which are known to occur in the endometrium and myometrium on Day 25 and 26 (Shaw, 1983b (Catling & Vinson, 1976). Since glucocorticoids stimulate PG synthesis by human amniotic cells (Potestio et ai, 1988), it is possible that corticosteroids secreted by the tammar fetus stimulate the release of PG from the placenta or endometrium by a similar mechanism, which then acts on the hypothalamus or pituitary to stimulate prolactin secretion.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Since it has been shown that the conceptus is associated with the peripartum prolactin peak (Tyndale-Biscoe et ai, 1988) the present results suggest that the fetus or its membranes induces this by initiating the release of PGs, which are known to occur in the endometrium and myometrium on Day 25 and 26 (Shaw, 1983b (Catling & Vinson, 1976). Since glucocorticoids stimulate PG synthesis by human amniotic cells (Potestio et ai, 1988), it is possible that corticosteroids secreted by the tammar fetus stimulate the release of PG from the placenta or endometrium by a similar mechanism, which then acts on the hypothalamus or pituitary to stimulate prolactin secretion.…”
Section: Discussionsupporting
confidence: 52%
“…Lewis et ai (1986) showed a large but brief pulse of PG to occur between 2 h before and 2 h after parturition and in 5 tammars the fall in progesterone occurred after the peak of PG. Shaw (1983b) found that the concentrations of PGF-2ot and PGE in uterine tissue increased from negligible amounts on Day 23 to maximum amounts on the expected day of parturition and then declined by 1 day post partum. Lewis et ai (1986) suggested that PG rather than prolactin is the agent of luteolysis, and that the prolactin peak is associated with the initiation of lactogenesis.…”
Section: Introductionmentioning
confidence: 92%
“…However, the progesterone pulse at reactivation stimulates an overall increase in uterine secretions and the activity of these factors can significantly affect the timing of blastocyst reactivation (Shaw & Renfree 1986, Spindler et al 1998. Therefore, there are numerous other uterine factors present, whose downstream effects could result in an increase in blastocyst PTAFR levels.…”
Section: Discussionmentioning
confidence: 99%
“…The tammar has a post-partum oestrus and the sucking stimulus of the pouch young acts to inhibit luteal development via prolactin secreted from the pituitary (reviewed in Tyndale-Biscoe & Renfree (1987)). This luteal inhibition prevents the progesterone pulse from occurring and results in the endometrium and subsequently the embryo entering into quiescence (Tyndale-Biscoe 1978, Shaw & Renfree 1986, Renfree & Shaw 2000. In this study, adult females with a pouch young older than day 8 post-partum were presumed to be carrying a diapausing blastocyst (Tyndale-Biscoe & Renfree 1987).…”
Section: Blastocystmentioning
confidence: 99%
See 1 more Smart Citation